Níveis de susceptibilidade de Chrysodeixis includens (Walker, [1858] Lepidoptera : Noctuidae) a Lufenuron e Espinosade - Queiroz, Lucas Ferraz de (2017)
Chrysodeixis includens is an important defoliation pest in crops such soybean and cotton in Brazil. Although its control has been done mainly by insecticides, there are no studies about susceptibly levels of this pest to insecticides. Therefore, the aim of this work was to evaluate the susceptibility levels of C. Includens populations in State of Mato Grosso to insecticides lufenurom and espinosade in order to supply basic information to management of active ingredients for controlling this species. Eight populations were collected in soybean crops and submitted to ingestion bioassays to determine their baselines. There were differences in susceptibility among C. includens populations in Mato Grosso. Although the molecules have different mechanisms of action, the population of Tangará da Serra had the highest resistance ratios for lufenurom (11.62) and Spinosad (7.84). Even those levels of resistance are considered low, it is necessary to keep a regional monitoring of susceptibility levels as well as to increase the range of molecules evaluated.